2018
DOI: 10.1007/s00464-018-6042-2
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic conversion in colorectal cancer surgery; is there any improvement over time at a population level?

Abstract: Conversion of laparoscopic colorectal cancer resection has been associated with worse outcome, but this might have been related to a learning curve effect. This study aimed to evaluate incidence, predictive factors and outcomes of laparoscopic conversion after the implementation phase of laparoscopic surgery at a population level. Patients undergoing elective resection of non-locally advanced, non-metastatic colorectal cancer between 2011 and 2015 were included. Data were extracted from the Dutch Surgical Colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 36 publications
(35 reference statements)
8
40
0
1
Order By: Relevance
“…A similar process could have occurred in Catalonia with rectal cancer, since we observed some selection bias favouring low-risk patients for laparoscopic surgery: this group was more likely to be younger than 80 years, have fewer comorbidities, present a lower ASA and be diagnosed at an earlier disease stage. The conversion rate observed in the present study (13.2%) is similar to that seen in the population-based study by de Neree et al [20] and the meta-analysis by Arezzo et al [11], and it is lower than that reported in a Spanish prospective non-randomized study [38].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A similar process could have occurred in Catalonia with rectal cancer, since we observed some selection bias favouring low-risk patients for laparoscopic surgery: this group was more likely to be younger than 80 years, have fewer comorbidities, present a lower ASA and be diagnosed at an earlier disease stage. The conversion rate observed in the present study (13.2%) is similar to that seen in the population-based study by de Neree et al [20] and the meta-analysis by Arezzo et al [11], and it is lower than that reported in a Spanish prospective non-randomized study [38].…”
Section: Discussionsupporting
confidence: 90%
“…The conversion rate observed in the present study (13.2%) is similar to that seen in the population‐based study by de Neree et al . and the meta‐analysis by Arezzo et al . , and it is lower than that reported in a Spanish prospective non‐randomized study .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These rates were significantly higher in those with late conversion (> 30 min) compared to early conversion (OR 1.34, 1.05-1.72). There was no impact of conversion on mortality in these patients [13]. In contrast, one of the largest series of segmental resections reported, with 207 311 patients operated in the United States, found that conversion had a higher morbidity and mortality than completed laparoscopic procedures, but better outcomes than primary open procedures [16].…”
Section: Discussionmentioning
confidence: 83%
“…Subsequently, several studies showed conversion rates between 10.4 and 29.0% with detrimental outcome [3,4,[13][14][15]. More recently, a Dutch national review reported a conversion rate of 8.6% for colon cancer [13]. The literature has been divided about whether conversion impacts detrimentally on short-term outcomes.…”
Section: Discussionmentioning
confidence: 99%